Levels and possible sources of heavy metals in surficial sediments of lake Vegoritis - ΣΚΟΥΛΙΚΙΔΗΣ, Ν. Θ. (Bulletin of the Geological Society of Greece, 2001)
Vegoritis is a large, deep, mesotrophic, typical karstic lake in ΝW Greece surrounded by mountains and Ptolemais Basin situated at its southern part. The Ptolemais Basin is subjected to the effluents of lignite mines, electric power generating plants, partly treated urban wastewaters, landfills, agricultural manufacturing units and agrochemicals from an extensively cultivated area. All these are carried into the lake through both, the atmosphere and surface runoff (Soulou River). The rock types of the mountainous part of the catchment area surrounding the lake are carbonates, acid metamorphic silicates and marble with schist and serpentinite, whereas the plain area is covered by fluviolacustrine pliocene, pleistocene and alluvial sedimentary formations. In order to identify the levels, and assess the origin of heavy metals in the surficial lake sediments 26 samples were collected using a grab sampler. Samples were analysed for their grain size, as well as for their mineral, organic matter, major element (Si02, A1203, Ti02, Fe203 , Kf>, Na20, CaO, MgO, P205, MnO, S) and heavy metal content (V, Cr, Mn, Co, Ni, Cu, Zn, As, Rb, Sr, Mo, Ba, Pb). Data were processed by multivariate statistical techniques and the main results and conclusions discussed. The heavy metals levels are low, when compared to nearly pristine lakes and normal soils. Even Cu, Pb and Zn, which are mainly derived from human activities, exhibit lower levels than in nearly pristine lakes. Only Ba, Cr, Ni and As are present in relatively high values. Ba is derived from the erosion of acid silicate rocks. Chromium originates primarily from the serpentinites and secondarily from pollution, whereas for Ni the opposite is true. The presence of As is due to fly ash deposition. The distribution of heavy metals in the lake sediments depends on lithology and pollution sources. Thus the southern part of the lake is enriched with V, Mn, Rb, Pb Fe and As from fly ash deposition. Cr, Co, Ni, Cu, Zn and Mo are derived through the Soulou R. outflow. In the northern part of the lake the weathering of acid silicate rocks contributes to the high concentrations of Ba, Rb and Sr. Considering the high anthropogenic pressure present in the area, the generally good environmental status of the lake, is attributed to its self purification potential resulting from the low retention time of the lake's water. Since As and Cr, depending on their valence state, can be considered as toxic and carcinogenic factors, a more detailed research study is suggested to be carried out.